Clinical Study of Computer-Assisted Cognitive Rehabilitation Training Combined with Repetitive Transcranial Magnetic Stimulation on Dysphagia in Patients with Mild Cognitive Impairment after Traumatic Brain Injury - LIU Ziao; SONG Xiaobian; ZANG Guangyue; ZHANG Chao; ZENG Xi (康复学报)
ObjectiveTo observe the effect of computer-assisted cognitive rehabilitation training (CACRT) combined with repetitive transcranial magnetic stimulation (rTMS) on dysphagia in patients with mild cognitive impairment after traumatic brain injury (TBI).MethodsA total of 64 dysphagic patients with mild cognitive impairment after TBI treated in the First Affiliated Hospital of Zhengzhou University from March 2021 to September 2023 were randomly divided into control group, magnetic stimulation group, cognitive group, and combined group, with 16 cases in each group according to the random function of Excel software. The control group received conventional swallowing function training; the magnetic stimulation group received rTMS treatment besides the conventional swallowing function training, targeting the affected hemisphere's motor cortex area for the mylohyoid muscle, at an intensity of 80% of the resting motor threshold (RMT), a frequency of 3 Hz, a stimulation duration for 2 s, and an intervals for 10 s; the cognitive group received CACRT in addition to the conventional swallowing function training, including attention, memory, spatial perception, emotion recognition, and visual feature perception training; the combined group received both rTMS and CACRT on top of the conventional swallowing function training, following the same methods as the magnetic stimulation group and the cognitive group. Each treatment session lasted 30 minutes a time, once a day, six days a week for two weeks. Before and after treatment, Standardized Swallowing Assessment (SSA) and Video Fluoroscopic Swallowing Study (VFSS) were used to evaluate swallowing function; the Mini-Mental State Examination (MMSE) was used to evaluate cognitive function.Results(1) SSA score: compared with that before treatment, SSA scores in the magnetic stimulation group, the cognitive group and the combined group after treatment decreased significantly (P<0.05). Compared with the control group, the magnetic stimulation group and the cognitive group, SSA score in the combined group after treatment was significantly lower (P<0.05). (2) VFSS score: compared with those before treatment, VFSS scores at oral, pharyngeal and esophageal phase in the control group, the magnetic stimulation group, the cognitive group and the combined group after treatment increased significantly (P<0.05). Compared with the control group, VFSS scores at esophageal phase in the magnetic stimulation group, VFSS scores at oral and pharyngeal phase in the cognitive group, VFSS scores at oral, pharyngeal and esophageal phase in the combined group after treatment increased significantly (P<0.05). Compared with the control group, the magnetic stimulation group and the cognitive group, VFSS scores at oral, pharyngeal and esophageal phase in the combined group after treatment increased significantly (P<0.05). (3) MMSE score: compared with that before treatment, MMSE scores in the control group, the magnetic stimulation group, the cognitive group and the combined group after treatment increased significantly (P<0.05). Compared with the control group, the magnetic stimulation group and the cognitive group, MMSE scores in the combined group after treatment increased significantly (P<0.05).ConclusionCACRT combined with rTMS can improve cognitive and swallowing function of patients with mild cognitive impairment and dysphagia after TBI, which is worthy of clinical promotion and application.